Pedoenvironments driving the monodominance of Peltogyne gracilipes (Leguminosae) in the Northern Amazon, Brazil - Angulo Villacorta, Carlos Darwin (2022)
Monodominance is unusual in the tropics when compared to the high diversity of tropical forests. Peltogyne gracilipes (Leguminosae) is a deciduous tree species that forms monodominant forests in the Brazilian Northern Amazon region. Initial research confirmed that P. gracilipes monodominance was associated with higher soil magnesium content, while recent studies have indicated a larger number of variables, suggesting a more complex hydro-edaphic habitat. As such, the present study aimed to describe the hydro-edaphic habitat (pedoenvironment) where P. gracilipes is monodominant. Edaphic and topographic variables (drainage proxy) were used in a forest inventory conducted in 129 sampling plots. Trees with a stem diameter greater than 10 cm were analyzed. Aboveground biomass was used as a descriptive variable of the different habitats in the study area. A total of 3041 individuals were sampled (298 P. gracilipes). Multivariate analysis demonstrated that the highest P. gracilipes abundance occurred in poorly drained (seasonal flooding) low-altitude habitats (<66 m), with high soil Fe+2 and Mg+2 concentrations. P. gracilipes monodominance in the study area is best described in habitats with more restricted hydro-edaphic conditions, where drainage is the primary factor and Fe+2 and Mg+2 are secondary agents resulting from the effect of seasonally drained soils. This study contributes to better understanding the environmental filters that characterize areas where P. gracilipes is more abundant, indicating that this species might potentially become monodominant in more restricted hydro-edaphic habitats in the Northern Amazon.